Relevance and perspectives of the use of chitosan in winemaking: a review. Issue 20 (13th November 2021) - Castro Marín, Antonio; Colangelo, Donato; Lambri, Milena; Riponi, Claudio; Chinnici, Fabio
Abstract: Chitosan is a natural polymer that has quite recently been approved as an aid for microbial control, metal chelation, clarification, and reduction of contaminants in enology. In foods other than wine, chitosan has also been evidenced to have some other activities such as antioxidant and antiradical properties. Nevertheless, the actual extent of its activities in must and wines has not been fully established. This review aimed to gather and discuss the available scientific information on the efficacy of chitosan as a multifaceted aid in winemaking, including antimicrobial, chelating, clarifying and antioxidant activities, while summarizing the chemical mechanisms underlying its action. Attention has been specifically paid to those data obtained by using unmodified chitosan in wine or in conditions pertinent to its production, intentionally excluding functionalized polymers, not admitted in enology. Unconventional utilizations together with future perspectives and research needs targeting, for example, the use of chitosan from distinct sources, production strategies to increase its efficacy or the potential sensory impact of this polysaccharide, have also been outlined.